National Security Complex and Networked Securitization in Cognitive Warfare - Alzaki Alzaki; Arfin Sudirman; R. Widya Setiabudi Sumadinata; Wawan Budi Darmawan; Ola Madallah Aljaafreh (Nusantara: Journal of Law Studies, 2026)
This article examines how cognitive warfare is securitized in Indonesia amid technological disruption and strategic competition in the Indo-Pacific region. Drawing on securitization theory, Just Securitization Theory, and Regional Security Complex Theory (RSCT), the study develops a multilevel analytical framework that connects global, regional, and domestic dynamics. Methodologically, it employs qualitative document analysis of defense policies, doctrinal publications, and relevant academic literature. The findings demonstrate that securitization in Indonesia is best understood as a networked and institutionally distributed process involving political leaders, military organizations, intelligence agencies, cybersecurity bodies, regulatory institutions, and societal actors. The study identifies an expansion of referent objects, extending beyond territorial sovereignty to include democracy, information sovereignty, social cohesion, and ideological stability. It further shows that cognitive warfare has shifted the primary battlespace toward perception, narrative construction, and psychological influence. As a key theoretical contribution, the article introduces the concept of the National Security Complex to capture intra-state dynamics of securitization. This framework reveals that securitization is not only multilevel but also multi-centered within the state apparatus. The study concludes that, although the securitization of cognitive threats is becoming increasingly institutionalized, it remains constrained by normative tensions concerning civil liberties and democratic accountability. By proposing the concept of the National Security Complex, this article also addresses a theoretical gap in RSCT, which has traditionally emphasized inter-state dynamics, thereby enabling a more structured understanding of security contestation at the domestic level.